At skrive til øret: Betragtninger fra en Storytel Originals-forfatter - Åberg, Daniel (Passage - Tidsskrift for litteratur og kritik, 2020)
The essay discusses the development of the audiobook from the author’s perspective. Åberg writes stories for the Storytel Originals series, which is produced specifically for the audiobook format by the audiobook service Storytel. He explains how writing directly for this format affects the author and how the text must be adjusted to the format. Furthermore, he discusses the cultural status of the author writing only, or primarily, for sound. He argues that since literary culture is still focused on the printed book, the audiobook author risks being overlooked or losing status.